DEGRADATION PROCESSES IN THE SEMI-ARID REGION: A SOCIO-ENVIRONMENTAL ANALYSIS - Maia, Eleide Leite; Alves, Adriana Ursulino (Seven Editora, 2026)
The depletion of natural resources, due to the increasing demand for agricultural and forestry products, combined with land use that disregards its potential and limitations, has led to the degradation of vegetation, soil, and water. The study of the vulnerability to which populations are exposed, as well as knowledge of land use capacity an important factor for proper soil management constitute essential elements for assessing the impacts on these areas. This study seeks information regarding socioeconomic, environmental, and drought-related vulnerabilities, as well as land use capacity in the northeastern semi-arid region. Furthermore, it highlights the need for planning and sustainable management guided by technical criteria and local realities, as indispensable strategies to mitigate degradation and promote the resilience of semi-arid populations. However, the adoption of appropriate land-use practices, combined with effective public policies, can contribute to the conservation of natural resources and to a more balanced and sustainable development of the region.